Efficacy and safety of different proprotein convertase subtilisin/kexin type 9 inhibitors in the general population and solid organ transplant recipients: a network meta-analysis - Luo, Bohan; Sun, Zhuang; Luo, Han (Frontiers in Pharmacology, 2025)
IntroductionWe conducted a network meta-analysis (NMA) to compare the efficacy (primarily assessed by low-density lipoprotein cholesterol (LDL-C) reduction and cardiovascular event (CVE) incidence) and safety (total adverse events (AEs), neurocognitive events (NCEs), injection site reactions, infections, and all-cause mortality (ACM)) of different Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors versus placebo in the general population and solid organ transplant (SOT) recipients.Materials and MethodsA total of 16 randomized controlled trials (RCTs) involving 79,615 patients were included. Cochrane risk of bias assessment tool evaluated the literature quality. Data analysis and graph generation were conducted employing RevMan5.3 and Stata20.0. The cumulative ranking probability curve (SUCRA) compared impact of different treatment regimens (DTRs) on patient efficacy, safety, and ACM.ResultsEvolocumab ranked highest for LDL-C reduction (SUCRA 67.2%) and CVE reduction (SUCRA 69.5%). Ongericimab had the lowest total AEs (SUCRA 91.3%), while Alirocumab ranked best for NCEs (SUCRA 89.5%) and infections (SUCRA 74.1%). Placebo had the fewest injection site reactions (SUCRA 89.8%). No PCSK9 inhibitor significantly reduced ACM (Alirocumab SUCRA 69.0%, highest but non-significant). LDL-C reduction was significant in both general and SOT populations, but CVE and ACM reductions were non-significant. Inclisiran increased risks of total AEs and injection site reactions (RR > 1.2).ConclusionEvolocumab is optimal for LDL-C and CVE reduction, while Ongericimab and Alirocumab offer better safety profiles. PCSK9 inhibitors did not increase acute rejection or infection risk in SOT recipients. Long-term mortality benefits remain uncertain.